PENGARUH NON PERFOMING LOAN, PRICE EARNING RATIO DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM - A.A Indah Cintya Devi Darma Danty; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2021)
Stock prices are defined with the market price .The market price is based in stock prices in today marketplace. Increase in the price of a stock has had a positive impact for the company because it can enhance the value of shares, god will negatively impact on company capital. The study aimed to identify the Non Performing Loan, Price Earning Ratio , and Price To Book Value on the price of shares in banking concerns listed at the indonesian stock exchange 2017-2019 years . Population in research the banking sector this is a company listed on the indonesia stock in 2017-2019 were 44 company. Sample dating techniques in research this is non sampling probabilitas use of purposive smpling. Sample use were 16 company, set the criteria upon. The of research is show that in partial Non Loan Perfoming can have negative effects and significantly to stock price, Price Earning Ratio influential and significantly to stock price. Price To Book Value and it has some positive effects on stock prices. In its simulatan , Non Perfoming Loan, Price Earning Ratio and Price To Book value influences on the banking concerns listed at the indonesian stock exchange .